Aktivitas Antioksidan Ekstrak Astaxanthin dari Limbah Kulit dan Kepala Udang Dogol (Metapenaeus ensis) - Winda Rahmalia; Adhitiyawarman Adhitiyawarman; Dwi Imam Prayitno; Yosef Novem Batistuta Lubis (Jurnal Kelautan Tropis, 2024)
Astaxanthin is a carotenoid derivative compound with various benefits, one of which is as an antioxidant, making astaxanthin applicable in drugs and cosmetics. Astaxanthin is discoverable in various sources, with shrimp as its main source. This study aims to determine the antioxidant activity of astaxanthin extracted from shrimp shell and head wastes. Extraction was carried out using the soxhletation method, followed by saponification to obtain free astaxanthin. Astaxanthin in extract before and after saponification were identified using thin-layer chromatography (TLC) and UV-Vis spectrophotometry. Antioxidant activity assay was carried out in five variations of sample concentrations using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method. Extraction of shrimp shell and head wastes resulted in an oil yield percentage of 1.02 and 3.05 % of dry mass in 60 g of shrimp shells, respectively. Identification results showed astaxanthin content in extracts after saponification were higher than that before saponification. There are three thin layer chromatography (TLC) separation spots and two UV-Vis absorption peaks in extracts before and after saponification. Antioxidant activity assay results (IC50) of shrimp shell extract before and after saponification showed antioxidant activity of 572.0 and 186.6 mg/L, respectively.